Effect of Monomer Composition on the Performance of Polymer‐Stabilized Liquid Crystals with Two‐Step Photopolymerization. Issue 17 (4th August 2019) - Zhang, Dongdong; Cao, Hui; Duan, Manyu; Wang, Huihui; Chen, Yinjie; Zong, Cheng; Gan, Ping; Zhao, Limin; Yang, Zhou; Wang, Dong; He, Wanli
ABSTRACT: Polymer‐stabilized cholesteric liquid crystal (PSCLC) films with broadband reflection based on two‐step photopolymerization are fabricated. Owing to the helical twisting power (HTP) value of the chiral dopant (CD) decreasing with increasing temperature, PSCLC films with broadband reflection are obtained by two‐step polymerization anchoring helical pitch of different length at two different temperature points. The effect of monomer composition on the PSCLC reflection properties before and after polymerization was studied. The results show that the free‐radical monomers with appropriate concentration and cationic monomers with sufficient concentration are vital for the formation of PSCLC films with broadband reflection. In addition, the experiments show that the increase in the functionality and rigidity of the cationic monomer has a positive effect on the broadening of the reflection band. This study can provide guidance and reference for the selection of monomer species and concentration in PSCLC preparation. © 2019 Wiley Periodicals, Inc. J. Polym. Sci., Part B: Polym. Phys.2019, 57, 1126–1132 Abstract : Polymer‐stabilized cholesteric liquid crystals (PSCLC) films with broadband reflection characteristics are prepared by two‐step photopolymerization. The effects of free‐radical monomer concentration, cationic monomer concentration, monomer functionality, and flexibility on the reflection properties of PSCLC films are investigated. It is observed that different monomer compositions result in different broadening effects on the reflective bands of the films.